MERAJUT KONEKSITAS DENGAN AL QUR'AN DI ERA DIGITAL: METODE DAN KEMAMPUAN INTELEKTUALITAS - Akib, Mohammad (STAI Pelabuhan Ratu, 2024)
This research reviews the challenges and solutions in building a connection with the Qur'an in the digital age, while presenting the necessary strategies and resources. In the context of the rapid development of information technology, individuals often experience distractions that hinder their relationship with the Qur'an. However, the digital era also offers a great opportunity to expand access and deepen understanding of the holy book of Islam. This research adopts a qualitative approach and literature review to explore methods and intellectual capabilities in strengthening the connection with the Qur'an in the digital era. This approach includes literature studies and content analysis to understand the effectiveness of using digital technology in enhancing spiritual relationships with the Qur'an. The aim of this research is to understand how digital technology can be effectively used to deepen spiritual relationships and understanding of the Qur'an, as well as to identify the challenges and solutions individuals face in utilizing this technology in their daily religious practices. The research results indicate that in the ever-evolving digital era, strengthening the connection with the Qur'an is essential for Muslims. The challenges and opportunities in deepening the relationship with the Qur'an in the digital age, as well as strategies and resources, are crucial. From technological distractions to innovations in learning, wise adaptation to technology supports the strengthening of spiritual bonds with the Qur'an. It is hoped that with the implementation of these strategies, Muslims can deepen their understanding of the Qur'an, strengthen religious practices, and enrich their religious identity in the continuously evolving digital age.